Harnessing the immunomodulatory effects of exercise to enhance the efficacy of monoclonal antibody therapies against B-cell haematological cancers: a narrative review - Collier-Bain, Harrison D.; Brown, Frankie F.; Causer, Adam J.; Emery, Annabelle; Oliver, Rebecca; Moore, Sally; Murray, James; Turner, James E.; Campbell, John P. (Frontiers in Oncology, 2023)
Therapeutic monoclonal antibodies (mAbs) are standard care for many B-cell haematological cancers. The modes of action for these mAbs include: induction of cancer cell lysis by activating Fcγ-receptors on innate immune cells; opsonising target cells for antibody-dependent cellular cytotoxicity or phagocytosis, and/or triggering the classical complement pathway; the simultaneous binding of cancer cells with T-cells to create an immune synapse and activate perforin-mediated T-cell cytotoxicity against cancer cells; blockade of immune checkpoints to facilitate T-cell cytotoxicity against immunogenic cancer cell clones; and direct delivery of cytotoxic agents via internalisation of mAbs by target cells. While treatment regimens comprising mAb therapy can lead to durable anti-cancer responses, disease relapse is common due to failure of mAb therapy to eradicate minimal residual disease. Factors that limit mAb efficacy include: suboptimal effector cell frequencies, overt immune exhaustion and/or immune anergy, and survival of diffusely spread tumour cells in different stromal niches. In this review, we discuss how immunomodulatory changes arising from exposure to structured bouts of acute exercise might improve mAb treatment efficacy by augmenting (i) antibody-dependent cellular cytotoxicity, (ii) antibody-dependent cellular phagocytosis, (iii) complement-dependent cytotoxicity, (iv) T-cell cytotoxicity, and (v) direct delivery of cytotoxic agents.